Formulação estratégica e controladoria no terceiro setor: uma abordagem por simulação de cenários - Hsu, Pang Lien (2015)
The third sector organizations are becoming increasingly indispensable in society, because it seeks to meet representative and competitive gain needs that otherwise would not be possible, therefore, the objective of this study is to analyze the variables that surrounds the current market of the Association of Micro and Small Business of Cascavel - AMIC for its strategic planning from scenarios simulation. For this, concepts about the strategic planning, strategy in nonprofit organizations, strategic tools, controlling and scenarios with adaptation to the model Rojo (2006) were raised. It is understood that the organization, despite it being non-profit, needs a strategic plan to remain competitive in the market. For that purpose, it will start with the a diagnosis by strategic tools of SWOT analysis, BCG matrix, Greiner s life Cycle, Porter Five Forces Analysis and Balanced Scorecard (BSC), which were all added in the simulation of scenarios in Rojo s model (2006) for the establishment of goals and targets for each simulated scenario, which will be audited and monitored from a controlling mechanism based on BSC. The strategies formulation and their controlling assisted in the survival and competitiveness of AMIC as well as clarified and helped to deepen our knowledge on strategic planning by scenarios applied to the specifics of nonprofit organizations